Bio-based Rigid Polyurethane Foam Prepared from Apricot Stone Shell-based Polyol for Thermal Insulation Application - Part 2: Morphological, Mechanical, and Thermal Properties - Fidan, Muhammed Said; Ertas, Murat (North Carolina State University, 2020)
The procedure for the liquefaction of apricot stone shells was reported in Part 1. Part 2 of this work determines the morphological, mechanical, and thermal properties of the bio-based rigid polyurethane foam composites (RPUFc). In this study, the thermal conductivity, compressive strength, compressive modulus, thermogravimetric analysis, flammability tests (horizontal burning and limited oxygen index (LOI)) in the flame retardants), and scanning electron microscope (SEM) (cell diameter in the SEM) tests of the RPUFc were performed and compared with control samples. The results showed the thermal conductivity (0.0342 to 0.0362 mW/mK), compressive strength (10.5 to 14.9 kPa), compressive modulus (179.9 to 180.3 kPa), decomposition and residue in the thermogravimetric analysis (230 to 491 °C, 15.31 to 21.61%), UL-94 and LOI in the flame retardants (539.5 to 591.1 mm/min, 17.8 to 18.5%), and cell diameter in the SEM (50.6 to 347.5 pm) of RPUFc attained from liquefied biomass. The results were similar to those of foams obtained from industrial RPUFs, and demonstrated that bio-based RPUFc obtained from liquefied apricot stone shells could be used as a reinforcement filler in the preparation of RPUFs, specifically in construction and insulation materials. Moreover, liquefied apricot stone shell products have potential to be fabricated into rigid polyurethane foam composites. © 2020. All Rights Reserved.
Keywords: Apricot stone shell; Characterization; Morphological properties; Rigid polyurethane foam; Thermal properties